2022
DOI: 10.3389/fvets.2022.857777
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Best Region for Measuring Eye Temperature in Dairy Cows Exposed to Heat Stress

Abstract: Eye temperature (ET) has long been used for predicting or indicating heat stress in dairy cows. However, the region of interest (ROI) and temperature parameter of the eye have not been standardized and various options were adopted by previous studies. The aim of this study was to determine the best ROI for measuring ET as the predictor of heat stress in dairy cows in consideration of repeatability and validity. The ET of 40 lactating Holstein dairy cows was measured using infrared thermography. The mean and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In the current study, no significant differences were found between the temperature of the right and left eyes before and after the race, which is confirmed by other studies in dogs and dairy cows [16,25]. The average minimum temperature for the eye region was statistically lower after running for both runs.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, no significant differences were found between the temperature of the right and left eyes before and after the race, which is confirmed by other studies in dogs and dairy cows [16,25]. The average minimum temperature for the eye region was statistically lower after running for both runs.…”
Section: Discussionsupporting
confidence: 89%
“…Difference between the responses of the lacrimal caruncle and lacrimal gland may also reflect the fact that the latter is irrigated by the infraorbital artery, a structure innervated by the sympathetic branch of the facial nerve (52, 58,60). Given these anatomical traits, these regions could be helpful for indirectly assessing autonomic nervous system activity as a stress response (61,62).…”
Section: Temperature Variation According To the Thermal Windowmentioning
confidence: 99%
“…The emissivity was set to 0.98, and the distance between the cow and the camera was approximately 1.5 m, in accordance with previous studies ( 29 ). We used eye temperature as a measure of BT, as confirmed in our previous study ( 30 ). Physiological indicator measurements were conducted twice daily on each of the 7 test days, with one measurement at 08:00 h to 09:00 h and the other at 14:00 h to 15:00 h in each period.…”
Section: Methodsmentioning
confidence: 99%